A Ferrocene‐Functionalized Covalent Organic Framework for Enhancing Chemodynamic Therapy via Redox Dyshomeostasis - Zhou, Le‐Le; Guan, Qun; Li, Wen‐Yan; Zhang, Zhiyong; Li, Yan‐An; Dong, Yu‐Bin (Small (Weinheim an der Bergstrasse, Germany), 2021)
Chemodynamic therapy (CDT), which induces cell death by decomposing high levels of H2O2 in tumor cells into highly toxic ·OH, is recognized as a promising antineoplastic approach. However, current CDT approaches are often restricted by the highly controlled and upregulated cellular antioxidant defense. To enhance ·OH‐induced cellular damage by CDT, a covalent organic framework (COF)‐based, ferrocene (Fc)‐ and glutathione peroxidase 4 (GPX4) inhibitor‐loaded nanodrug, RSL3@COF–Fc (2b), is fabricated. The obtained 2b not only promotes in situ Fenton‐like reactions to trigger ·OH production in cells, but also attenuates the repair mechanisms under oxidative stress via irreversible covalent GPX4 inhibition. As a result, these two approaches synergistically result in massive lipid peroxide accumulation, subsequent cell damage, and ultimately ferroptosis, while not being limited by intracellular glutathione. It is believed that this research provides a paradigm for enhancing reactive oxygen species‐mediated oncotherapy through redox dyshomeostasis and may provide new insights for developing COF‐based nanomedicine. Versatile covalent organic frameworks (COFs)! The organic nanodrug RSL3@COF–Fc (2b), which integrates the glutathione peroxidase 4 inhibitor RSL3 and Fenton‐like reaction catalyst ferrocene (Fc) into a nanoscale COF, induces ferroptosis to enhance chemodynamic therapy by blocking lipid repair and disrupting cellular redox homeostasis.